Immediate effect of intravitreal injection of bevacizumab on intraocular pressure - Lemos-Reis R; Moreira-Gonçalves N; Melo AB; Carneiro AM; Falcão-Reis FM (Clinical Ophthalmology, 2014)
Ricardo Lemos-Reis,1 Nuno Moreira-Gonçalves,1 António B Melo,1 Ângela M Carneiro,1,2 Fernando M Falcão-Reis1,2 1Department of Ophthalmology of Hospital de São João, Porto, Portugal; 2Department of Sense Organs, Faculty of Medicine, University of Porto, Porto, Portugal Purpose: To investigate the immediate effect of intravitreal injection of bevacizumab on intraocular pressure (IOP). Methods: This was a prospective and nonrandomized study. A total of 291 eyes with macular edema or active choroidal neovascularization were submitted to a single 1.25 mg (0.05 mL) bevacizumab intravitreal injection. Intraocular pressure was measured with an Icare® tonometer immediately before and after injection in a seated position. The presence of subconjunctival reflux was recorded. The fellow eye served as the control.Results: Mean preoperative IOP was 18.0±5.9 mmHg in the treated eye versus 16.9±6.0 mmHg in the fellow eye. Mean postoperative IOP was 42.1±14.5 mmHg in the treated eye versus 17.5±6.0 mmHg in the fellow eye. The IOP variation was statistically significant in both cases and controls (P<0.001 and P=0.003, respectively), and this increase was higher in cases than in controls (P<0.001). Postoperative IOPs higher than 50 mmHg were achieved in 32.0% of the eyes. Subconjunctival reflux was present in 21.3% and determined a lower IOP rise (P<0.001). Tested variables (glaucoma, phakic status, and sex) did not have a statistically significant effect on IOP rise or subconjunctival reflux. Conclusion: IOP increases with intravitreal bevacizumab injection, reaching 50 mmHg or more in about one third of patients. A higher IOP is expected if no subconjunctival reflux occurs. The baseline IOP does not influence the incidence of subconjunctival reflux. The clinical relevance of these facts has yet to be clarified. Keywords: bevacizumab, intraocular pressure, intravitreal injection, Icare®